Treatment of leachate by electrocoagulation using aluminum and iron electrodes - Ilhan, Fatih; Kurt, Ugur; Apaydin, Omer; Gonullu, M. Talha (ELSEVIER, 2008)
In this paper, treatment of leachate by electrocoagulation (EC) has been investigated in a batch process. The sample of leachate was supplied from Odayeri Landfill Site in Istanbul. Firstly, EC was compared with classical chemical coagulation (CC) process via COD removal. The first comparison results with 348 A/m(2) current density showed that EC process has higher treatment performance than CC process. Secondly, effects of process variables such as electrode material, current density (from 348 to 631 A/m(2)), pH, treatment cost, and operating time for EC process are investigated on COD and NH4-N removal efficiencies. The appropriate electrode type search for EC provided that aluminum supplies more COD removal (56%) than iron electrode (35%) at the end of the 30 min operating time. Finally, EC experiments were also continued to determine the efficiency of ammonia removal, and the effects of current density, mixing, and aeration. All the findings of the study revealed that treatment of leachate by EC can be used as a step of a joint treatment. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: electrocoagulation; iron and aluminum electrodes; leachate; mixing and aeration; unit treatment cost; WASTE-WATER TREATMENT; LANDFILL LEACHATE; ELECTROCHEMICAL OXIDATION; DYE SOLUTIONS; REMOVAL; COAGULATION; DECOLORIZATION; WASTEWATERS; FLOTATION; COD; Engineering; Environmental Sciences & Ecology